Conceptualising of Muslims’ in using Ar-Rahnu services offered by Malaysian Islamic banks / Muhammad Haris Naqiuddin Muda ... [et al.] - Naqiuddin Muda, Muhammad Haris; Rahmat, Ainol Mardhiyah; A. Rahim, Nur Rifhan; Abd Halim, Siti Noorhaslina; Mohamad Razali, Nur Hanisah; Md Dali, Hafizuddin (UiTM Cawangan Johor, 2024)
This paper aims to recognize and discuss the factors influencing the intention of Muslims to participate in Ar-Rahnu offered by Islamic banks. Despite conventional pawnshops offering a higher margin to the value of collateral higher asset values in loans compared to Ar-Rahnu, there has been a noticeable increase in the demand for Ar-Rahnu over the years. The discussions attempt to create a discourse around the factors that influence the intention of Muslims to participate in Ar-Rahnu by using the Theory of Planned Behaviour plus religiosity. The findings propose conceptual frameworks that consist of components such as attitudes, subjective norms, perceived behavioral control, and religiosity as factors influencing the intention of Muslims to participate in Ar-Rahnu. However, these frameworks remain conceptual and await validation through empirical testing by future researchers. The findings of this study will provide valuable insights for Malaysian Islamic banks to enhance their Ar-Rahnu services. By aligning their offerings with Muslims' preferences and needs, Islamic banks can foster stronger relationships with their customer base and potentially attract new clientele. This review is hoped to be valuable to the present and future Ar-Rahnu scholars interested in the evolution of literature and identifying opportunities for future research. Ultimately, this paper addresses the crucial question of the factors influencing Muslims' intention to participate in Ar-Rahnu services in Islamic banks, thus contributing to the advancement of knowledge in this field.